Kritik Ali Syariati atas Kebebasan tanpa Transendensi dalam Humanisme Eksistensialis Jean-Paul Sartre - Dhani Wahyu Maulana; Tien Rohmatin; Kusen Kusen (Paradigma: Jurnal Kalam dan Filsafat, 2026)
This article examines Ali Shariati’s critique of freedom without transcendence in Jean-Paul Sartre’s existentialist humanism. This library-based study employs critical conceptual analysis of Sartre’s and Shariati’s principal works on humanism, freedom, and the human being. The findings demonstrate that Sartre understands the human being as freedom that forms its essence and values through choices without a predetermined purpose. Shariati does not reject human freedom but criticizes its separation from a transcendent foundation and social responsibility. Through his theomorphic anthropology, he understands the human being as constituted by clay and the spirit of God, called to overcome four forms of imprisonment and assume the responsibility of the vicegerent. The article argues that Shariati’s critique is not merely a theological rejection of Sartrean atheism but a reconstruction of radical freedom into transcendent freedom connecting self-creation, ethical orientation, love, and social transformation.